Asosiasi antara Jenis Tempat Penampungan Air (TPA) dan Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kota Surakarta - Prasasti, Nita; Sumardiyono, .; Probandari, Ari N (Nexus Kedokteran Komunitas, 2013)
Background: Dengue Hemorrhagic Fever (DHF) is a health problem in Indonesia, which has been the potential to be the cause of epidemic, because of its widespread distribution from year to year. One of the factors considered to influence the incidence of DHF is the condition of water container, which includes the type of landfill, landfill color, and size of the landfill. However, these factors are limited studied in the laboratory and still little information gained from field research until now. This study aimed to investigate the association between type of water container and the occurance of DHF in the city of Surakarta. Methods: This study was an observational study particularly a matched case-control design. It was conducted from June to October 2012 at five health centers located in the city of Surakarta. The total sample size was 68 subjects (34 subjects as cases with DHF, and 34 other subjects as free-DHF controls). Data were analyzed using McNemar test. Results: The study found a stastical significant relationship between the type of water container and DHF occurance with odds ratio of 7.5 (p= 0.001; CI 95% 1.715-32.79). Conclusion: There is a stastical significant association between the occurance of DHF and type of water container in the city of Surakarta. The use of non-cheramik type water container, increases a persons risk for DHF at 7.5 times higher. Keywords: DHF, type of water container, color of water container